2023
DOI: 10.3390/toxins15020147
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Botulinum Toxin B in Focal Hyperhidrosis: A Narrative Review

Abstract: Botulinum toxin type B (BoNT-B), known as Myobloc® in the United States and as Neurobloc® in Europe, is a new therapeutically available serotype among the botulinum toxin family. During the last years several data have been reported in literature investigating its efficacy and safety, as well as defining the dosing and application regiments of BoNT-B in the treatment of hyperhidrosis. Moreover, recent studies have been examining its safety profile, which may be different from those known about BoNT-A. The aim … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…18 Botulinum toxin (BTX) acts by blocking the acetylcholine at the neuromuscular synapse, it exhibits a quicker onset of action but a shorter duration, usually patients responded to treatment until month 6. 19 We think that even though the cost of Miradry treatment is more than the rest of the modalities the long lasting or even permanent results present an advantage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Botulinum toxin (BTX) acts by blocking the acetylcholine at the neuromuscular synapse, it exhibits a quicker onset of action but a shorter duration, usually patients responded to treatment until month 6. 19 We think that even though the cost of Miradry treatment is more than the rest of the modalities the long lasting or even permanent results present an advantage.…”
Section: Discussionmentioning
confidence: 99%
“…Topical anticholinergics are an emerging therapeutic class in the treatment of focal hyperhidrosis, and one study indicated that 2% glycopyrronium bromide cream is effective for 12 weeks of application in patients with axillary bromhidrosis, but one patient reported irritation at the site of application and another reported mydriasis, which resolved spontaneously 18 . Botulinum toxin (BTX) acts by blocking the acetylcholine at the neuromuscular synapse, it exhibits a quicker onset of action but a shorter duration, usually patients responded to treatment until month 6 19 . We think that even though the cost of Miradry treatment is more than the rest of the modalities the long lasting or even permanent results present an advantage.…”
Section: Discussionmentioning
confidence: 99%
“…Subcutaneous neurotoxins such as botulinum toxin are especially useful for hyperhidrosis following amputation because a single treatment can last 3 to 6 months, whereas topicals must be applied multiple times per day and can be inherently irritating to the skin. 27,62 Furthermore, ablative fractional…”
Section: Postamputation Dermatologic Concernsmentioning
confidence: 99%
“…These patients consistently express feeling ostracized from their community and anxious about unemployment, leaking fluid, or odor from the wound, as well as other social stigmata. 62 Depression and anxiety can hinder a patient's ability to care for their wound and make them more susceptible to the myriad issues that can ensue.…”
Section: Postamputation Dermatologic Concernsmentioning
confidence: 99%
“…The mechanism of action of Botulinum toxin involves the inhibition of acetylcholine release at the neuromuscular junction, leading to a temporary reduction in sweating [ 11 ]. In the context of facial hyperhidrosis, BTA injections into the affected areas can significantly reduce sweat production, improving comfort and social interactions [ 12 ]. Several studies have highlighted the utility of BTA in reducing symptoms of hyperhidrosis, with a favorable safety profile [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%